Looking for the active hydrogen species in a 5 wt% Pt/C catalyst: a challenge for inelastic neutron scattering. (29th May 2018) - Carosso, M.; Lazzarini, A.; Piovano, A.; Pellegrini, R.; Morandi, S.; Manzoli, M.; Vitillo, J. G.; Ruiz, M. Jimenez; Lamberti, C.; Groppo, E.
Abstract : We looked at the active hydrogen species in a highly dispersed and very homogeneous 5 wt% Pt/C industrial catalyst (Pt particle mean diameter of 2.0 ± 0.5 nm) for hydrogenation reactions, by coupling H2 adsorption measurements with Inelastic Neutron Scattering (INS). Abstract : We looked for the active hydrogen species in a highly dispersed and very homogeneous 5 wt% Pt/C industrial catalyst (Pt particle mean diameter of 2.0 ± 0.5 nm) for hydrogenation reactions, by coupling H2 adsorption measurements with Inelastic Neutron Scattering (INS). Taking advantage of the enormous progress undergone by INS instruments, we succeeded in collecting INS spectra of unprecedented quality that allowed us to: (1) demonstrate that the Pt nanoparticles are mainly located at the regular edges of the sp 2 graphitic domains on the activated carbon; (2) validate that most of the H2 physisorbed on the carbon is side-on adsorbed; (3) detect for the first time H2 molecules adsorbed on hydride-covered Pt nanoparticles; (4) observe Pt–hydrides (on the Pt/C catalyst with the lowest Pt loading among those investigated by INS so far) and (5) provide evidence for the occurrence of spillover of atomic hydrogen from the Pt surface to unsaturated reactive sites located at the irregular borders of the sp 2 domains on the activated carbon.